The 50-g glucose challenge test and pregnancy outcome in a multiethnic Asian population at high risk for gestational diabetes - Tan, P.C. (2009)
Objective: To evaluate the 50-g glucose challenge test (GCT) on pregnancy outcome in a multiethnic Asian population at high risk for gestational diabetes (GDM). Methods: GCT was positive if the 1-hour plasma glucose level was >= 7.2 mmol/L. GDM was diagonsed by a 75-g glucose tolerance test using WHO (1999) criteria. Of the 1368 women enrolled in the study, 892 were GCT negative, 308 were GCT false-positive status was associated with preterm birth (adjusted odds ration AOR 2.1; 95% CI, 3.3-7.5), cesarean delivery (AOR 2.5; 95% CI, 1.6-3.2), postpartum hemorrhage (AOR 2.1; 95% CI, 1.2-3.7), and neonatal macrosomia (AOR 2.5; 95% CI, 1.0-6.0). Conclusion: GCT false-positive women had an increased likelihood of an adeverse pregnancy outcome. The role and threshold of the GCT needs re-evaluaion. (C) 2008 International Federation of Gynecology and Obstetrics. Published by Elsevier Ireland Ltd. All rights reserved.